TESTING OF BLACK SOYBEAN SEED RESPONSE TO SALINITY STRESS IN GERMINATION STAGE - Halimursyadah Halimursyadah; hasanuddin hasanuddin; munanzar noorman (UNEJ e-Proceeding, 2017)
The objective of this research is to know the response of black soybean seed to salinity stress in germination stage and also to identify the interaction between the two factors. This research has been conducted from April to August 2016 at the Laboratory of Seed Science and Technology of the Faculty of Agriculture, Syiah Kuala University. The experiment was designed using a Factorial Random Block Design. The first factor was the four national varieties of black soybeans (Detam 1, Detam 2, Mutiara 2 and Mutiara 3) and the second factor was the concentration of NaCl (0; 2; 4; 6; 8; and 10 g L-1). There are 24 treatment combinations each repeated three times. The parameters observed were viability (maximum growth potential, germination and time to reach 50% of total germination) and vigor of growing strength (vigor index, relative growth rate, synchrony growth, primary root length of normal seedling germination and dry weight of normal seedling germination. The study showed that Detam 2 were more tolerant than other varieties based on all viability and vigor parameters of growing strength observed. The increase in NaCl concentration at level 4 g L-1 had a very significant effect on the observed parameters indicated by the decrease of viability value and vigor of growing strength. There was a very significant interaction between varieties and concentration of NaCl to viability and vigor of soybean seedling growth that is at the maximum growth potential, primary root length of normal seedling germination and dry weight of normal seedling germination.